ADDITIONAL SUPPORT FOR RELATIVE WAVELENGTH INDEPENDENCE OF IR LAGS IN NGC 4151 OVER THE PAST DECADE - Oknyansky, V. L; Shenavrin, V. I.; Metlova, N. V.; Gaskell, C. M. (Одеські астрономічні публікації, 2018)
We present results of a study of the correlation between the infrared (JHKL) and optical (B) ﬂuxes of the nucleus of the Seyfert galaxy NGC 4151 for the years 2010–2015 using our own data (partially published) in combination with published data [1, 2, 3, 4]. We ﬁnd similar lags for each of the HKL passbands relative to the optical of 37 ± 3 days. The lags are the same to within the accuracy of measurement. We do not conﬁrm a signiﬁcant decrease in the lag for HKL in 2013–2014 previously reported by SchnЁulle et al. [4], but we ﬁnd that the lag of the short-lag component of J increased. We discuss our results within the framework of the standard model, where the variable infrared radiation is mainly due to the thermal re-emission of short-wave radiation by dust clouds close to a variable central source. There is also some contribution to the IR emission from the accretion disk, and this contribution increases with decreasing wavelength. The variability in J and K is not entirely simultaneous, which may be due to the diﬀering contributions of the radiation from the accretion disk in these bands. The absence of strong wavelength-dependent changes in infrared lag across the HKL passbands can be explained by having the dust clouds during 2010–2015 be located beyond the sublimation radius. The relative wavelength independence of the infrared lags is also consistent with the hollow bi-conical outﬂow model of Oknyansky et al. [5].